2019
DOI: 10.3346/jkms.2019.34.e263
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Digital Media Use in Korean Preschool Children

Abstract: BackgroundChildren today are exposed to various media devices, and their usage of these is increasing. Prior studies have outlined forms of harm this can potentially cause. However, there has been little empirical research on the use of media devices among preschool children in Asia. The aim of this study was to examine and analyze longitudinal trends in media device use among Korean preschool children, focusing on the frequency of engagement, time spent with, and ownership of media devices, delineated by sex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
(35 reference statements)
0
17
0
2
Order By: Relevance
“…Our previous study shows an increase in the tendency of media device use and its adverse effects among preschool children in Korea. 3 4 5 Online learning has many advantages of education equalities but high risks for online exposures. In this study, only 6.9% of parents reported that their children's online learning activities did not go well and it is fortunate that online education was relatively well-working.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study shows an increase in the tendency of media device use and its adverse effects among preschool children in Korea. 3 4 5 Online learning has many advantages of education equalities but high risks for online exposures. In this study, only 6.9% of parents reported that their children's online learning activities did not go well and it is fortunate that online education was relatively well-working.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited 217 caregivers of primary school children, including 97 children who had already participated in the Kids Cohort for Understanding of Internet Addiction Risk Factors in Early Childhood (K-CURE) study, 11 from community centers in Suwon City, Gyeonggi Province, South Korea. Parents who contacted the study team were e-mailed a link to the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This prospective cohort study was conducted in Korea to investigate the effects of internet usage on children and adolescents. Our study used the first wave data of the K-CURE study [ 17 ]. The data were collected between December 1, 2015, and June 30, 2016, on the mothers of 400 children aged two through five years old recruited from three cities (Suwon, Goyang, and Seongnam).…”
Section: Methodsmentioning
confidence: 99%